Pemetaan Penyebaran Penyakit Demam Berdarah Dengue (DBD) di Kota Jambi Tahun 2018 – 2022 - Hidayati, Fajrina; Solida, Adila; Wisudariani, Evy; Rahmat, Andree Aulia (Jurnal Riset Hesti Medan, 2023)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that is influenced by the environment and people's behavior. In Jambi City, Dengue Fever is still a public health problem. This research aims to determine the relationship between environmental factors and the incidence of dengue fever in Jambi City in 2018 - 2022. This research uses Global Moran's analysis and Local Indicator of Spatial Association (LISA) to determine the Hot Spot and Cold Spot areas for dengue cases in Jambi City in 2018 -2022 with a sub-district analysis unit of 62 sub-districts. During 5 years of observation, the results showed that the distribution pattern of dengue fever cases was clustered in 2018-2022. The results of research on the distribution of dengue fever cases from 2018-2022 showed that the lowest cases were in 2021, namely 132 cases, while the highest cases were in 2019, 698 cases. Subdistricts with the HH (High-High) category are referred to as DBD Hot Spot areas, where subdistricts that have high dengue cases are surrounded by high dengue cases, which were also found in 2018, namely Bagan Pete, Rawasari, and Murni subdistricts. In 2019, namely Suka Karya, Paal Lima, Kenali Asam Bawah, Mayang Mangurai, Bagan Pete, Talang Bakung, Payo Selincah and Eka Jaya Villages. In 2020, Pasir Putih, Simpang III Sipin, Paal Lima, Mayang Mangurai, Bagan Pete, Beliung, Talang Bakung, Payo Selincah, and Paal Merah subdistricts. In 2021, namely Thehok Village, Kenali Asam Bawah, Mayang Mangurai, Bagan Pete. In 2022, namely the sub-districts of Pasir Putih, Thehok, Paal Lima, Kenali Asam Bawah, Kenali Asam Atas, Talang Bakung, Lingkar Selatan, and Paal Merah. By knowing the distribution pattern of dengue fever, you can determine regional priorities in implementing intervention programs to prevent and control dengue fever in the Jambi city.